1985
DOI: 10.1007/bf02294245
|View full text |Cite
|
Sign up to set email alerts
|

An examination of procedures for determining the number of clusters in a data set

Abstract: classification, stopping rules, numerical taxonomy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
1,920
3
67

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,184 publications
(2,000 citation statements)
references
References 45 publications
10
1,920
3
67
Order By: Relevance
“…These included the 'C-index' (Hubert & Levin 1976) and Davies & Bouldin (1979) 'Validity Index' which both examine the similarity of clusters. These measures have both been shown to be effective at determining the correct number of clusters (Milligan & Cooper 1985). Ad hoc measures 'mean distance of cases to their cluster centre' (indicating compactness of clusters) and 'average cluster size'…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included the 'C-index' (Hubert & Levin 1976) and Davies & Bouldin (1979) 'Validity Index' which both examine the similarity of clusters. These measures have both been shown to be effective at determining the correct number of clusters (Milligan & Cooper 1985). Ad hoc measures 'mean distance of cases to their cluster centre' (indicating compactness of clusters) and 'average cluster size'…”
Section: Resultsmentioning
confidence: 99%
“…The gradient of each measure was examined to identify the 'knee point' in the trend of increasing number of solutions. Where there is a large improvement in the model, followed by a flattening of the trend, this would indicate that further improvements in the number of clusters are not adding much more understanding to the classification (Milligan & Cooper 1985). Comparing the measures in Figure 1 suggested that an eight cluster solution was most appropriate for capturing the variations in the data as it performed most efficiently across each measure.…”
Section: Resultsmentioning
confidence: 99%
“…Although no universally valid solution is available, there are a few criteria that have been studied in depth and seem to perform reasonably well. We have chosen here the Calinski and Harabasz index which, according to Milligan and Cooper (1985), is one of the best in given situations. This index is computed from the between and pooled within sum of squares.…”
Section: Methodsmentioning
confidence: 99%
“…other criteria exist, such as those described by (Milligan and Cooper, 1985) and (Charrad et al, 2014). In our own current method for EEG microstate segmentation (freely available software Cartool (https://sites.google.com/site/cartoolcommunity/), we propose a metacriterion based on several different criteria taken from the literature.…”
Section: Defining the Number Of Clustersmentioning
confidence: 99%